Two Unpublished Sphinxes of Amenemhat V and Ramses II - El-Mezain, Mohamed.
This article publishes two headless sphinxes, now in the Open Panorama site near the Al-Nasr Gate of Old Cairo. According to inscriptions and stylistic features, one sphinx belonged to King Amenemhat V of Dynasty 13. His monuments are scanty despite his four or five years of rule. The other sphinx belongs to Ramses II of the Dynasty 19. Its inscribed offering table is unique. The statues originally ornamented a sphinx avenue of the temple of Heliopolis. Then they were reused as a lintel for a side gate and a threshold of the Ayyubid Walls of Old Cairo during the medieval period. This paper presents the two sphinxes from the walls of Old Cairo and tries to determine from where they were brought to Old Cairo, and how they were transported to their present location. http://dx.doi.org/10.5913/jarce.55.2019.a0006